2020
DOI: 10.1038/s41598-020-78294-2
|View full text |Cite
|
Sign up to set email alerts
|

Maternal immune activation induces sustained changes in fetal microglia motility

Abstract: Maternal infection or inflammation causes abnormalities in brain development associated with subsequent cognitive impairment and in an increased susceptibility to schizophrenia and autism spectrum disorders. Maternal immune activation (MIA) and increases in serum cytokine levels mediates this association via effects on the fetal brain, and microglia can respond to maternal immune status, but consensus on how microglia may respond is lacking and no-one has yet examined if microglial process motility is impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 78 publications
9
64
0
1
Order By: Relevance
“…These aspects, which are still not clarified, are of crucial relevance also for predicting the possible impact of the current pandemics in the neurodevelopmental trajectories of the next generation. Different processes have been brought into play to explain the effect of MIA on the offspring neurodevelopment, including (but not limited to) the altered expression of genes involved in neuronal migration [29] and the generation of an abnormal cortical phenotype [30], changes in the intrinsic excitability of neurons [18,31], impaired spine and synaptic development [32][33][34], and altered activation of microglia [35,36]. Notably, disturbances of the neurovascular unit (NVU) physiology and brain vasculature morphology have been identified as one of the leading causes of several neurological diseases, both in developing and aged brain.…”
Section: Introductionmentioning
confidence: 99%
“…These aspects, which are still not clarified, are of crucial relevance also for predicting the possible impact of the current pandemics in the neurodevelopmental trajectories of the next generation. Different processes have been brought into play to explain the effect of MIA on the offspring neurodevelopment, including (but not limited to) the altered expression of genes involved in neuronal migration [29] and the generation of an abnormal cortical phenotype [30], changes in the intrinsic excitability of neurons [18,31], impaired spine and synaptic development [32][33][34], and altered activation of microglia [35,36]. Notably, disturbances of the neurovascular unit (NVU) physiology and brain vasculature morphology have been identified as one of the leading causes of several neurological diseases, both in developing and aged brain.…”
Section: Introductionmentioning
confidence: 99%
“…GD9 also occurs at a time at which the fetal brain is undergoing extensive neural proliferation and migration, which transitions more towards circuit refinement and cortical organization by GD17 (our late MIA-timepoint) (58). Importantly, microglia may play important roles in the regulation of apoptosis (59) as well as the permeability and formation of the blood-brain barrier, which typically takes shape between GD13.5-15.5 in the mouse. Apoptosis is a critical cellular process in early brain and placental development in utero (60).…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, maternal inflammation is thought to result in elevated pro-inflammatory cytokines that can cross the placental barrier and access placental cells via maternal blood in the SAs and intervillous spaces, influencing the fetal brain development [ 160 ]. Studies have shown that maternal immune activation (MIA) induced sustained alterations in motility patterns of fetal microglia, which may contribute to subsequent risks for cognitive diseases [ 161 ]. Moreover, it has been demonstrated that MIA may lead to an increase in Th17 cells in maternal serum, which can be associated with ASD-related cortical and behavioral abnormalities in the offspring [ 113 ].…”
Section: Pregnancy and Sars-cov-2 Infectionmentioning
confidence: 99%